2018
DOI: 10.1089/neu.2017.5540
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of Microglia to the M2 Phenotype in a Peroxisome Proliferator-Activated Receptor Gamma–Dependent Manner Attenuates Axonal Injury Induced by Traumatic Brain Injury in Mice

Abstract: Increasing evidence indicates that activated microglia play an important role in the inflammatory response following traumatic brain injury (TBI). Inhibiting M1 and stimulating M2 activated microglia have demonstrated protective effects in several animal models of central nervous system diseases. However, it is not clear whether the polarization of microglia to M2 attenuates axonal injury following TBI. In this study, we used a lateral fluid percussion injury device to induce axonal injury in mice. Mice were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 51 publications
2
55
0
Order By: Relevance
“…As a widely used antidiabetic drug which works as an insulin sensitizer by binding to the PPAR‐γ in fat cells, RSG may also serve as a master gatekeeper in CNS injury and repair . It is emerging that the PPAR‐γ is constitutively expressed in microglia and activating PPAR‐γ in microglia may regulate the phenotypic change of microglia . PPAR‐γ activation could favor a reprogramming process of microglia toward a beneficial phenotype, with anti‐inflammatory and tissue‐repair properties .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a widely used antidiabetic drug which works as an insulin sensitizer by binding to the PPAR‐γ in fat cells, RSG may also serve as a master gatekeeper in CNS injury and repair . It is emerging that the PPAR‐γ is constitutively expressed in microglia and activating PPAR‐γ in microglia may regulate the phenotypic change of microglia . PPAR‐γ activation could favor a reprogramming process of microglia toward a beneficial phenotype, with anti‐inflammatory and tissue‐repair properties .…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] It is emerging that the PPAR-γ is constitutively expressed in microglia and activating PPAR-γ in microglia may regulate the phenotypic change of microglia. [40][41][42][43] PPAR-γ activation could favor a reprogramming process of microglia toward a beneficial phenotype, with antiinflammatory and tissue-repair properties. [10][11][12][13]44 Interestingly, previous studies have shown that 1 day after ischemia, the microglia/macrophages adopt an anti-inflammatory phenotype that progressively evolves toward a neurotoxic phenotype at day 7 poststroke.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, HMGB1 is also reported to be an important mediator of inflammation in epilepsy models and has potential as a predictive biomarker of epileptic seizures . Rosiglitazone, a potent peroxisome proliferator‐activated receptor γ (PPARγ) agonist with anti‐inflammatory properties, has been reported to induce M2 polarization in a TBI model in mice, attenuating axonal injury and improving neurological function . However, improved TBI outcomes by rosiglitazone may also involve other biological mechanisms, such as limiting the mitochondrial dysfunction and oxidative damage, as well as suppressing autophagy .…”
Section: Approaches To Induce Microglia M2 Polarization: Potential Agmentioning
confidence: 99%
“…10,84 Rosiglitazone, a potent peroxisome proliferator-activated receptor γ (PPARγ) agonist with anti-inflammatory properties, has been reported to induce M2 polarization in a TBI model in mice, attenuating axonal injury and improving neurological function. 85 However, improved TBI outcomes by rosiglitazone may also involve other biological mechanisms, such as limiting the mitochondrial dysfunction and oxidative damage, as well as suppressing autophagy. 86,87 Previous studies also suggest that PPARγ agonists provide neuroprotection and suppress development of epileptic seizures in animal models of temporal lobe epilepsy.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…Peroxisome proliferator activated receptor gamma (PPAR-γ) plays an important role in regulating transcription expression of anti-inflammatory cytokines . Studies have shown that PPAR-γ agonists (pioglitazone or rosiglitazone) can switch the transition of microglia cells from a proinflammatory to an anti-inflammatory state , Wen et al, 2018. Natural compounds have broad prospects in neuroimmune regulation.…”
Section: Introductionmentioning
confidence: 99%